To Buy or Not to Buy? Price Salience in an Online Shopping Field Experiment - Markus Dertwinkel-Kalt; Mats Köster; Matthias Sutter (Institute of Labor Economics (IZA), 2020)
We examine whether shrouding or partitioning of a surcharge raises demand in online shopping. In a field experiment with more than 34,000 consumers, we find that consumers in the online shop of a cinema are more likely to select tickets for a 3D movie when the 3D surcharge is shrouded, but they also drop out more often when the overall price is shown at the checkout. In sum, the demand distribution is independent of the price presentation. This result outlines the limits of the effectiveness of shrouding practices.
Keywords: D81; C93; 330; salience; inattention; shrouding; price partitioning; field experiment